Steel fiber performance in reinforced concrete deep beams with mid-span web opening - Sharifah Maszura, Syed Mohsin; Hammood, Rasheed Abed; Nur Farhayu, Ariffin; Khairunisa, Muthusamy; Saffuan, Wan Ahmad (Semarak Ilmu Publishing, 2025)
Opening on reinforced concrete beams is sometimes crucial to allow for the pipelines of electrical circuits. These openings will affect the strength and ductility of the beams. This paper presents the effect of adding steel fiber to cater the loss due to the mid-span web opening in reinforced concrete deep beams. Two amount of fibers volume fractions was considered (1% and 2%) with two different opening shapes (square and rectangular). One beam without opening was casted as a control beam. On the other hand, three beams with square opening and three beams with rectangular opening were also casted. Each beam catered for each amount of steel fiber content of 0%, 1% and 2%. The beams were tested under four-point bending test to failure. It was observed that the size or shape of the opening greatly decreased the beams' ability to support loads. Additionally, the strength and ductility of the reinforced concrete deep beams with mid-span web opening were enhanced by the inclusion of steel fiber, which made them similar to the control beam (without opening).